2017
DOI: 10.1002/pon.4440
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of doctors' and nurses' barriers to communicating with seriously ill patients about their dependent children

Abstract: Our study indicates (1) the need to use templates and manual procedures to gather and process information about children in medical records; (2) the need for managerial backing for addressing children of seriously ill patients and time spent on it; and (3) the need for future HP training programmes to include how to implement procedures and how to address all barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(97 citation statements)
references
References 13 publications
2
94
0
1
Order By: Relevance
“…Patients also have their individual preferences—some wanting healthcare professionals’ advice as how to inform their children about their illness, others not wanting to discuss problems concerning their children. Therefore, discussing patients’ children is not only about identifying healthcare professionals’ barriers and how to overcome them (Dencker et al, ; Turner et al, ). We suggest that it is also about identifying patients’ preferences and needs being aware of patients’ different identities and the dynamics between them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients also have their individual preferences—some wanting healthcare professionals’ advice as how to inform their children about their illness, others not wanting to discuss problems concerning their children. Therefore, discussing patients’ children is not only about identifying healthcare professionals’ barriers and how to overcome them (Dencker et al, ; Turner et al, ). We suggest that it is also about identifying patients’ preferences and needs being aware of patients’ different identities and the dynamics between them.…”
Section: Discussionmentioning
confidence: 99%
“…This qualitative study was part of a larger study of the interaction of healthcare professionals with seriously ill patients about patients' dependent children, including 49 interviews with doctors and nurses, 15 patient interviews and 27 days of participant observations within haematology, gynaecological oncology and neuro-intensive care (Dencker et al, 2017). This paper focuses on patients' experiences and is based on the interviews with patients and on participant observations, including observations of encounters between patients and healthcare professionals.…”
Section: Me Thodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural barriers also exist, as identified by Dencker, Rix, Bøge, and Tjørnhøj‐Thomsen (), investigating communication with seriously ill patients about their dependent children. They indeed found that elements such as “lack of space in the medical record system, professional code, time pressure, and lack of training” constitute significant barriers.…”
Section: Resultsmentioning
confidence: 99%